The Effect of Mall Strategy Integrated with Padlet Towards Students’ Reading Comprehension - Prastya, I Gede Yoga (Universitas Pendidikan Ganesha, 2019)
The research aimed at investigating the significant difference on students’ reading comprehension between students taught using Mobile Assisted Language Learning (MALL) strategy integrated with Padlet and students taught using conventional teaching strategy. This research was quasi-experimental utilizing post-test only control group design. The population of this research was tenth-grade students in SMA Negeri 4 Singaraja. The sample of this research were 73 students consisting of 35 students from X BB 1 as experimental group and 38 students from BB 2 as control group. The sample were chosen using cluster random sampling technique. The data collection in both groups were done through post-test. The obtained data were analyzed using descriptive and inferential statistical analysis. The result of descriptive statistics analysis reveals that the mean score for experimental group is higher than control group (78.03 > 73.39). Furthermore, the result of inferential statistics analysis through t-test shows that the significant value of tobserve is higher than tcritical value, which is 2.270 > 1.666 (df = 71, α = 0.05). Thus, it indicates that there is a significant difference on students’ reading comprehension between students taught using Mobile Assisted Language Learning (MALL) strategy integrated with Padlet and students taught using conventional teaching strategy.